2019
DOI: 10.3390/catal9110896
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Effect of Microbead Size Distribution on the Kinetics of Heterogeneous Biocatalysts through Single-Particle Analysis Based on Fluorescence Microscopy

Abstract: Understanding the functionality of immobilized enzymes with spatiotemporal resolution and under operando conditions is an unmet need in applied biocatalysis, as well as priceless information to guide the optimization of heterogeneous biocatalysts for industrial purposes. Unfortunately, enzyme immobilization still relies on trial-and-error approximations that prevail over rational designs. Hence, a modern fabrication process to achieve efficient and robust heterogeneous biocatalysts demands comprehensive charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Despite this narrow range, we still observed that the V o of immobilized Bs-ADH slightly decreased as the particle size increased ( Figure S11A ). This is consistent with the previous bulk 48 and single-particle studies 23 that show similar effects. Remarkably, the immobilized Bs-ADH concentration negatively correlated with the particle radius; therefore, smaller microbeads loaded higher enzyme concentrations, resulting in higher single-particle initial rates ( V o ) ( Figure S11B ).…”
Section: Results and Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Despite this narrow range, we still observed that the V o of immobilized Bs-ADH slightly decreased as the particle size increased ( Figure S11A ). This is consistent with the previous bulk 48 and single-particle studies 23 that show similar effects. Remarkably, the immobilized Bs-ADH concentration negatively correlated with the particle radius; therefore, smaller microbeads loaded higher enzyme concentrations, resulting in higher single-particle initial rates ( V o ) ( Figure S11B ).…”
Section: Results and Discussionsupporting
confidence: 93%
“…The functional dispersion among beads found in Figures 4 and 5 encouraged us to investigate the particle-to-particle functional dispersion in commercial carriers like agarose porous microbeads. 23 Through monitoring single-particle reaction courses, we study the effects of protein concentration on the apparent kinetic parameters of immobilized enzymes toward their confined cofactors. As a model system for these studies, we selected RhB-labeled Bs-ADH co-immobilized with NADH on AG-Co 2+ /E-PAH microbeads with particle radius size ranging from 40 to 60 μm.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last years, our groups have been able to co-immobilise different alcohol dehydrogenases and ketoreductases with their corresponding redox cofactors. 26,27,62 As result, we obtain self-sufficient heterogeneous biocatalysts, which require no exogenous supply of NAD(P)H. Harnessing the PEI layer needed to stabilise the quaternary structure of Tt27-HBDH, we co-immobilised the NADH with the enzyme through ionic interactions (AG-G@Tt27-HBDH(PEI-NADH)). The cofactor was effectively bound to the agarose microbeads in less than 15 min (Fig.…”
Section: Fabrication and Kinetic Characterization Of Self-sufficient Heterogeneous Biocatalysts Of Tt27-hbdhmentioning
confidence: 99%